The Federalist papers - Hamilton, Alexander, 1757-1804.; Madison, James, 1751-1836.; Jay, John, 1745-1829.; Rossiter, Clinton, 1917-1970.; Kesler, Charles R. (New York, NY : Signet Classic, 2003)
Three early American statesmen defend the political principles and ideologies set forth in the Constitution of the United States, in a new edition of the classic, which is accompanied by a selected bibliography, historical glossary, new introduction, andother resource material.
Introduction -- A note on this edition -- The Federalist Papers -- Contents of the Federalist -- Preface -- The Declaration of Independence -- The Articles of Confederation -- The Constitution of the United States of America, collated with The Federalist Papers -- Notes on The Federalist Papers -- Selected bibliography -- Index of ideas
Includes bibliographical references and index.
Keywords: Constitutional history -- United States -- Sources; Constitutional law -- United States; Constitutional history; Constitutional law; United States; Sources